Kebaya: Belenggu Konservatif Perempuan Muslim - Fitrayani Dian Rositadewi (Jurnal Hawa : Studi Pengarus Utamaan Gender dan Anak, 2020)
Kebaya as clothing that is identical to Indonesian identity has undergone changes in line with modernization. This change, apart from encouraging adaptations that must be carried out by women, also has implications for female values. This paper explains how changes in the existence and use of the kebaya as women's clothing have become the basis for the values and norms imposed on women. Kebaya modifications in various forms also become a configuration that forms the inherent values of women. Given that the kebaya is also the clothing of Muslim women, the kebaya has presented an interaction between culture and religion in its use. In other words, the times that were adapted to clothing have also changed perceptions of women's identity.